How John Lennon’s "No Religion" Instantiates Religion: A Symbolic Analysis a la the Brothers Pageau - Taylor, Matthew (Anthropoetics, 2024)
John Lennon’s “Imagine” is an extraordinarily successful song that has become a secular anthem. Not surprisingly, its message often aggravates religious believers, who do not appreciate the invitation to imagine “no religion.” In this reflection I engage the anti-religious thrust of “Imagine” from a different angle, following the symbolic worldview of Jonathan and Matthieu Pageau. The project of the Pageau brothers is to reclaim the symbolic grammar of the ancient world, which they hold to be as true for us now at the phenomenological level as it ever was. However, we do not apprehend this symbolic language and thus operate with blinkered vision, including when approaching religion and the biblical text, no matter how religious or irreligious we are. “Imagine” is a striking demonstration of this. From the symbolic perspective of the Pageaus, the paradox is that it asks us to imagine no religion while at the same time it instantiates religion. Even this iconic anti-religious hymn is, to use Jonathan Pageau’s phrase, “nested in religion.” In almost every line, “Imagine” expresses itself as religion, puts forward religious propositions, and assume a religious structure. Ironically, the religious elements woven so skillfully (if unintendedly) into “Imagine” may explain why it continues to grip so many and never goes out of style. Yet, as a symbolic analysis makes clear, the message of the song undercuts itself. For instance, from the very first line—from a symbolic perspective—there could by definition be no “imagine” without “heaven.” Lennon’s religious intuition (what the song enacts) is extremely astute, while his religious imagination (what the song is about) is deeply impoverished. Yet the same could be said of the religion Lennon putatively opposes, and both reflect the hollowed-out imagination of modernity. Indeed, as moderns, we all suffer this poverty of imagination to a greater or lesser degree. Turning to generative anthropology (GA), we have what could be considered a very “modernist” project. Yet, its view of humanity as “the symbolic species” (to borrow Terrence Deacon’s phrase) seems quite resonant with the symbolic perspective of the Pageaus. This is especially so because, for them, symbolism and the sacred are ultimately about attention. The resonance between the symbolic worldview and generative anthropology is considered in this reflection, as well as some possible incompatibilities, and get particular focus in the conclusion.